The Influence of Information Technology Utilization on Service Effectiveness at BPJS Employment - Muin, Sri Adrianti; Indrayanti, Evi; Aldiansyah, Andi; Tamsil, Erni (Generasi Sains Indonesia, 2025)
In this paper, the author considers the effects of information technology (IT) application on the service effectiveness at BPJS Employment, one of the major providers of social insurance in Indonesia. Quantitative method was used to collect data using structured questionnaires to 120 respondents, of which 120 are staff and the remaining are service users. Inferential statistical tests such as correlation and regression analysis have indicated that IT utilization and service effectiveness have strong and significant positive relationship. According to the regression model, the use of IT was used to explain the difference in the service effectiveness with a standardized coefficient of 0.742 and p-value of less than 0.001. The results indicate that online registration, automated claims, and mobile systems enhance greatly the value of service, efficiency, speed, and accuracy. The findings offer empirical information regarding e-governance procedures in Indonesia, which is important to supplement the current literature that mostly focuses on qualitative approaches. The study, with a quantitative analysis, contributes to the debate on the way digital tools can change the public service institutions. In general, the study shows that it is imperative to empower IT infrastructures, to train its users, and to advocate digital literacies to continue to streamline service delivery and to make the public sector institutions in Indonesia sustainable.